Exploring intergenerational knowledge transfer within Inuvialuit families: connecting wellbeing, food security, and climate resiliency - Ramirez Prieto, Maria; Ostertag, Sonja; Donnelly, Tamara; Wolki-Ruben, Celina; Arey, Shayla; Memogana, Susie; Slack, Camille; Skinner, Kelly (Frontiers in Climate, 2026)
IntroductionToday in the Inuvialuit Settlement Region, Canada, many community members are closely connected to and dependent on the land, with 68.9% of Indigenous people in the ISR indicating that they fished and harvested in 2023. Access to cultural practices and activities with family and on-the-land has been identified as vital to food sovereignty, food security, and wellbeing.MethodsThis study, using a foodways transmission lens, documents Inuvialuit families’ experiences with CF and subsistence harvesting, including the intergenerational transmission of Inuvialuit Knowledge, which support food sovereignty and wellbeing. Using a community-based action research approach, we partnered with community organizations and community researchers to conduct nine family-group interviews with participants (n = 28) across Aklavik, Tuktoyaktuk, and Ulukhaktok, representing two to three generations (youth, middle-aged adults and Elder).ResultsReflexive thematic analysis identified four themes: (1) Learning on the land through experiences; (2) Nourished by the land; (3) Navigating barriers; and (4) Inuit guiding principles for present and future generations’ wellbeing. Findings highlight that extended time on the land as a family fosters holistic nourishment, harvesting and survival skills, and skills for “living a good life,” while systemic and climatic changes constrain these opportunities for families. Families emphasized guiding principles such as sharing, environmental stewardship, and adaptability as key for keeping present and future generations healthy.DiscussionThe information provided in this paper is not new to Inuvialuit. It is provided for the benefit of evidence for programs, policies, and services, as well as for non-Inuvialuit audiences to better understand the importance of family, subsistence harvesting, the transmission of Inuvialuit Knowledge, and culture to food security and wellbeing.